Pengaruh Harga, Kualitas Produk dan Promosi terhadap Keputusan Pembelian pada Outlet Starbucks (Studi Kasus Pondok Indah Mall) - Situmeang, Rina Defitri; Widayati, Christine Catur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Modern society, especially millennials, has a lifestyle that keeps up with the times. Gathering in cafes with friends and co-workers has become one of today's lifestyles. Best seller food and beverage offerings in cafes are usually accompanied by supporting facilities such as wifi and instagramable interior design. Every year, the Indonesian coffee industry experiences very rapid growth. At first, Indonesians were used to sipping coffee. Coffee is a big and significant trend. From how to make a cup of coffee to how to enjoy it properly and in a fashionable way. The increase in cafes in Indonesia has an effect on increasingly fierce competition. Every cafe must be able to innovate in order to survive and not lose competitiveness with other cafes. One of the types of cafes that have sprung up is a coffee shop or coffee shop. Companies are more likely to consider ways to encourage repurchasing interest of their goods and services when there is intense competition. The approach that researchers use in this study is quantitative. The population of this study is Starbucks consumers and the sample used is 132 people. Data collection techniques in this study using a questionnaire. The data analysis method in this study is the Component or Variance Based Structural Equation Model using the PLS version of the Partial Least Square (Smart-PLS) program. The results of the study stated that price, product quality and promotion had a positive and significant effect on purchasing decisions for Starbucks products.